Health Promotion Strategy On Increasing Public Knowledge Regarding Early Detection Of Tuberculosis At The Fransisco Borja Da Costa Fatuberliu State High School, Manufahi Regency - Otniel Deswan Cristanto (International Journal of Health Engineering and Technology, 2026)
Tuberculosis remains a significant public health problem, particularly among adolescents with varying levels of health literacy. This study aimed to improve the school community's knowledge about early tuberculosis detection at Fransisco Borja Da Costa Fatuberliu State High School, Manufahi Regency. This study used a community service design with a school-based health education approach. The population was all students at the school, while the sample was selected purposively based on participation criteria. The research instruments included pretest and posttest sheets, educational materials, and participant observation. Data were analyzed descriptively by comparing the results before and after the intervention. The results showed an increase in student knowledge after the health education was provided, accompanied by good participation during the session. It was concluded that the school-based health promotion strategy was effective in improving student knowledge about early tuberculosis detection and can be used as a preventive approach in the school environment.